Quality of life and outcome of patients with metastatic pancreatic cancer receiving first‐line chemotherapy with nab‐paclitaxel and gemcitabine: Real‐life results from the prospective QOLIXANE trial of the Platform for Outcome, Quality of Life and Translational Research on Pancreatic Cancer registry. Issue 6 (23rd October 2020) - Al‐Batran, Salah‐Eddin; Hofheinz, Ralf‐Dieter; Reichart, Alexander; Pauligk, Claudia; Schönherr, Caroline; Schlag, Rudolf; Siegler, Gabriele; Dörfel, Steffen; Koenigsmann, Michael; Zahn, Mark‐Oliver; Schubert, Jörg; Aldaoud, Ali; et al.
Abstract: Few data exist on health‐related quality of life (QoL) in patients with metastatic pancreatic cancer (mPC) receiving first‐line chemotherapy (Awad L ZE, Mesbah M Boston, MA. Applying survival data methodology to analyze quality of life data, in Mesbah M, Cole BF, Ting Lee M‐L (eds): Statistical Methods for Quality of Life Studies: Design, Measurements and Analysis. Kluwer Academic Publishers 2002). The QOLIXANE study is a prospective, noninterventional, multicenter substudy of the Platform for Outcome, Quality of Life and Translational Research on Pancreatic Cancer (PARAGON) registry, which evaluated QoL in patients with mPC receiving first‐line gemcitabine and nab‐paclitaxel chemotherapy in real‐life setting. QoL was prospectively measured via EORTC QLQ‐C30 questionnaires at baseline and every month thereafter. Therapy and efficacy parameters were prospectively collected. Main objectives were the rate of patients without deterioration of Global Health Status/QoL (GHS/QoL) at 3 and 6 months. Six hundred patients were enrolled in 95 German study sites. Median progression‐free survival was 5.9 months (95% confidence interval [CI], 5.2‐6.3). Median overall survival (OS) was 8.9 months (95% CI, 7.9‐10.2), while median time to deterioration of GHS/QoL was 4.7 months (95% CI, 4.0‐5.6). With a baseline GHS/QoL score of 46 (SD, 22.8), baseline QoL of the patients was severely impaired, in most cases due to loss in role functioning and fatigue. In the Kaplan‐Meier analysis, 61% and 41% of patients had maintained GHS/QoL after 3 and 6 months, respectively. However, in the QoL response analysis, 35% and 19% of patients had maintained (improved or stable) GHS/QoL after 3 and 6 months, respectively, while 14% and 9% had deteriorated GHS/QoL with the remaining patients being nonevaluable. In the Cox regression analysis, GHS/QoL scores strongly predicted survival with a hazard ratio of 0.86 ( P < .0001). Patients with mPC have poor QoL at baseline that deteriorates within a median of 4.7 months. Treatment with gemcitabine and nab‐paclitaxel is associated with maintained QoL in relevant proportions of patients. However, overall, results remain poor, reflecting the aggressive nature of the disease. What's new?: In metastatic pancreatic cancer (mPC), chemotherapy with nab‐paclitaxel plus gemcitabine has shown significant survival benefits. However, less attention has been paid to quality of life (QoL) for these patients. In this prospective study, the authors found that, due to the aggressive nature of mPC, QoL declined rapidly for most patients. But surprisingly, as many as 41% of patients were able to maintain their baseline QoL at six months. Thus, while overall results remain poor, it does appear possible to stabilize QoL for a subset of patients receiving this first‐line combination chemotherapy.